Identity dynamic, action and context - Costalat-Founeau, Anne Marie (2007)
Social identity should not be considered anymore as a fixed and static image that defines individual or collective representations. It is embedded within a representational dynamic where biographical and social phases left their marks. This social imprint is partly made by the experience ingrained in the remembrance that gives all its experiential reality to identity. Action participates and reinforces this concreteness. It seems that the prescriptive nature of action reinforces its presence and therefore its effects. More precisely, these effects, which are inherent to action, possess a central power in the identity dynamic. Action is at the heart of subjectivity in the sense that it connects aspirations, representations, as well as the values of the individual and the sense of his own capacity. It involves the tight interweaving of affective and cognitive factors interacting into dynamic regulations and organizing more or less conflicting identity phases. We present in this article the effects of action on subjectivity.